2012
DOI: 10.1002/ls.1185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser textured dimples on the lubrication performance of cylinder liner in diesel engine

Abstract: Laser surface texturing (LST) technique was utilised on a cylinder liner in a diesel engine. In order to analyse the effect of LST micro‐dimples on the lubrication and friction properties of cylinder liner–piston ring (CL–PR), we developed a new mixed lubrication model on the basis of the average Reynolds equation and asperity contacts equation. The model can consider the coupling effects between the surface roughness of non‐texturing regions and micro‐dimples and the synergistic effects of multi‐micro‐dimples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 16 publications
3
40
0
Order By: Relevance
“…In this situation, the total lateral thrust force consists of the lateral thrust force of oil film and lateral thrust force of solid-solid contact and the total friction force consists of the oil film shear stress and asperity shear stress. The ratio of oil film thickness is normally used to evaluate the lubrication condition; when ≥ 4, the piston skirt-cylinder liner system is under hydrodynamic lubrication condition; when < 4, the piston skirtcylinder liner system is under mixed-lubrication condition, and asperity contact [38] is inescapable.…”
Section: Solid-to-solid Contact Modelmentioning
confidence: 99%
“…In this situation, the total lateral thrust force consists of the lateral thrust force of oil film and lateral thrust force of solid-solid contact and the total friction force consists of the oil film shear stress and asperity shear stress. The ratio of oil film thickness is normally used to evaluate the lubrication condition; when ≥ 4, the piston skirt-cylinder liner system is under hydrodynamic lubrication condition; when < 4, the piston skirtcylinder liner system is under mixed-lubrication condition, and asperity contact [38] is inescapable.…”
Section: Solid-to-solid Contact Modelmentioning
confidence: 99%
“…Making use of Reynolds model, Gadeschi et al [44], and later Checo et al [21] employing Elrod-Adams model, showed that for a fixed load it is possible to obtain a configuration that minimizes the friction only for moderate R/L (≈ 10) or higher. These results are in agreement with pioneering experiments made by Costa & Hutchins [31], and with latter studies by Tomanik [85,86], Kovalchenko et al [60], Yin et al [90], Scaraggi et al [81], among others [33,2,50].…”
Section: Algorithm 4: Dynamic Gauss-seidel For Reynolds Equation Withsupporting
confidence: 92%
“…For instance, there are several works (both numerical and experimental) where textured surfaces are described by h being discontinuous [91,90,82,21]. For handling this, we need to look beyond the classical definition of derivative: here is where the tools of Functional Analysis appear.…”
Section: Weak Formulation For Reynolds Equationmentioning
confidence: 99%
“…The resulting engine systems must also meet the strict emissions and fuel economy targets that have been recently established. 7) One of the main factors in the durability and tribological behavior of engine components and lubricants is fuel characteristics. 8) New engines tend to require improved diesel fuel lubricity to avoid excessive wear of the fuel injection system.…”
Section: Introductionmentioning
confidence: 99%